Governance principles for the wildlife trade to reduce spillover and pandemic risk - Duan Biggs; Alison J. Peel; Christos Astaras; Alexander Braczkowski; Hubert Cheung; Chi-Yeung Choi; Robinson Diotoh Orume; Hernán Cáceres-Escobar; Jacob Phelps; Raina K. Plowright; Jacques Rooyen; Julia Velden; et al. (CABI, 2023)
Abstract The COVID-19 pandemic and its aftermath are the most significant socio-economic crises in modern history. The pandemic's devastating impacts have prompted urgent policy and regulatory action to reduce the risks of future spillover events and pandemics. Stronger regulatory measures for the trade of wildlife are central to discussions of a policy response. A variety of measures, including broad bans on the trade and sale of wildlife to banning specific species for human consumption are among a suite of discussed options. However, the wildlife trade is diverse, complex, and important for the livelihoods of millions of people globally. We argue that reducing the risk of future pandemics stemming from the wildlife trade must follow established principles of governance which include being equitable, responsive, robust, and effective. We demonstrate how incorporating these principles will support the development of context-specific, culturally sensitive, and inclusive responses that recognize the on-the-ground complexity of disease emergence and the social-ecological systems in which the wildlife trade occurs.